The Enterprise Resource Planning System and Human Influences on Perceived Business Benefits - Lim, Jiansi; Mohamed, Norshidah; Shahriza Abdul Karim, Nor (International Journal of Engineering and Technology, 2018)
Strategic information systems are designed to support business processes for firms to achieve competitive advantage in the market place. Enterprise Resource Planning (ERP) system is one such example of a strategic information system. While there have been many re-searches on ERP systems, evidence about ERP systems business benefits from user’s perspective still remains to be known. The research, therefore, aims at exploring and determining the influences of ERP systems on business benefits. The influences encompass the user satisfaction with the ERP system itself (system factor) and the human factor of service provider as perceived by users. The human factor is made up of the perceived service quality of provider as consultant and the relationship quality between the user and the provider. Data was collected using a survey research instrument from three different organizations in Malaysia. A total of 120 users provided responses to the survey. The research provides support for the ERP system and human influences on user’s perceived business benefits. Implica-tions of the research are discussed herein
Keywords: Strategic Information Systems; Enterprise Resource Planning Systems; Exploratory Analysis; Survey Research